StuA-Regulated Processes in the Dermatophyte Trichophyton rubrum: Transcription Profile, Cell-Cell Adhesion, and Immunomodulation - Bitencourt, Tamires A.; Neves-da-Rocha, João; Martins, Maira P.; Sanches, Pablo R.; Lang, Elza A. S.; Bortolossi, Julio C.; Rossi, Antonio; Martinez-Rossi, Nilce M. (Frontiers in Cellular and Infection Microbiology, 2021)
Fungal infections represent a significant concern worldwide, contributing to human morbidity and mortality. Dermatophyte infections are among the most significant mycoses, and Trichophyton rubrum appears to be the principal causative agent. Thus, an understanding of its pathophysiology is urgently required. Several lines of evidence have demonstrated that the APSES family of transcription factors (Asm1p, Phd1p, Sok2p, Efg1p, and StuA) is an important point of vulnerability in fungal pathogens and a potential therapeutic target. These transcription factors are unique to fungi, contributing to cell differentiation and adaptation to environmental cues and virulence. It has recently been demonstrated that StuA plays a pleiotropic role in dermatophyte pathophysiology. It was suggested that it functions as a mediator of crosstalk between different pathways that ultimately contribute to adaptive responses and fungal-host interactions. The complex regulation of StuA and its interaction pathways are yet to be unveiled. Thus, this study aimed to gain a deeper understanding of StuA-regulated processes in T. rubrum by assessing global gene expression following growth on keratin or glucose sources. The data showed the involvement of StuA in biological processes related to central carbon metabolism and glycerol catabolism, reactive oxygen species metabolism, and cell wall construction. Changes in carbohydrate metabolism may be responsible for the significant alteration in cell wall pattern and consequently in cell-cell interaction and adhesion. Loss of StuA led to impaired biofilm production and promoted proinflammatory cytokine secretion in a human keratinocyte cell line. We also observed the StuA-dependent regulation of catalase genes. Altogether, these data demonstrate the multitude of regulatory targets of StuA with a critical role in central metabolism that may ultimately trigger a cascade of secondary effects with substantial impact on fungal physiology and virulence traits.